Analyzing the outcomes of China's ecological compensation scheme for development-related biodiversity loss - Gao, S; Bull, JW; Baker, J; zu Ermgassen, SOSE; Milner-Gulland, EJ (Wiley, 2023)
Over the past three decades, China's government has implemented many projects under its ecological compensation policy, including paying compensation fees for habitat creation to redress natural habitat losses caused by development. However, a critical evaluation of both the policy design and its ecological outcomes, has not previously been carried out. We assemble diverse data sources to provide the first evaluation of China's eco-compensation policy and practice, identifying several challenges. In policy, the pricing of forest restoration fees is insufficient in several provinces, and there is no requirement for use of biodiversity metrics or for ecological equivalence of compensation and losses. In practice, only 23% of a sample of 31 developments applied quantitative biodiversity metrics, and fewer than 1% of China's local governments have disclosed information regarding compensation implementation. Thus, to improve the validity of its compensation policy and practice to better secure biodiversity, China may need to embrace higher compensation standards, having first prevented ecological losses where possible. Equally important, China may also need to improve compensation governance for data tracking and conservation effectiveness monitoring.